Application Therapy of Warm Water Foot Soak with a Mixture of Salt and Red Ginger (Zingiber officinale Roscoe) on Lower Blood Pressure in Hypertension Patients - Iskandar Muda; Maya Wayamay Tiara Liyanti; Khumaidi; Mayusef Sukmana (Fakultas Kedokteran, Universitas Mulawarman, 2023)
Background: Approximately 1.56 billion adults in 2020 suffer from hypertension, and 8 million die yearly. Treating non-pharmacological hypertension with warm water foot soak therapy combined with salt or red ginger (Z. officinale Roscoe) can help blood circulation smoothly. Purpose: The study aimed to compare the application of warm water foot soak therapy with a mixture of salt and red ginger (Z. officinale Roscoe) to reduce blood pressure in hypertensive patients. Methods: The method used is descriptive with a case study approach on four respondents with hypertension. The measuring instrument used to measure blood pressure is a digital tensimeter. Results: Blood pressure decreased in four respondents before therapy, soaking feet in warm water with a mixture of salt and red ginger (Z. officinale Roscoe) respectively R1 = 140/98 mmHg, R2 = 150/90 mmHg, R3 = 149/99 mmHg, R4 = 158/96 mmHg and after six consecutive days of water foot soak therapy R1 = 133/88 mmHg, R2 = 129/80 mmHg, R3 = 129/85 mmHg, R4 = 130/88 mmHg. Conclusion: Therapy soaking feet in warm water with a mixture of salt and red ginger (Z. officinale Roscoe) is effective for lowering blood pressure, but it is recommended to use red ginger (Z. officinale Roscoe). Keywords: Hypertension, Warm Water Foot Soak Therapy, Salt, Red Ginger (Zingiber officinale Roscoe)